The Effect of Self Medication Practices on Oversight of Potent Drugs Without a Doctor's Prescription - Masaliha, Musyafar T; Alwi, Sabir; Misdar, Andriani (Universitas Muhammadiyah Surabaya, 2023)
The practice of self-medication is the practice of treating oneself without consulting a doctor. The practice of self-medication according to existing regulations may only be carried out for over the counter drugs and limited over the counter drugs, however, in practice in the field there are many self medication practices using hard drugs without a doctor's prescription. This study aims to analyze the practice of self-medication of hard drugs without a doctor's prescription legally and to analyze its relationship with the supervision carried out by the POM Agency. This study uses a normative juridical method by analyzing cases that occur using existing legal materials, both primary, secondary and non-legal materials. From the research it can be concluded that the practice of self-medication of potent drugs without a doctor's prescription is contrary to existing provisions and can affect the effectiveness of the implementation of supervision carried out by the BPOM.Â